Optimization of DNA polymerase mutation rates during bacterial evolution - Loh, Ern; Salk, Jesse J; Loeb, Lawrence A (Proceedings of the National Academy of Sciences - PNAS, 2010)
Mutation rate is an important determinant of evolvability. The optimal mutation rate for different organisms during evolution has been modeled in silico and tested in vivo, predominantly through pairwise comparisons. To characterize the fitness landscape across a broad range of mutation rates, we generated a panel of 66 DNA polymerase I mutants in Escherichia coli with comparable growth properties, yet with differing DNA replication fidelities, spanning 10³-fold higher and lower than that of wild type. These strains were competed for 350 generations in six replicate cultures in two different environments. A narrow range of mutation rates, 10- to 47-fold greater than that of wild type, predominated after serial passage. Mutants exhibiting higher mutation rates were not detected, nor were wild-type or antimutator strains. Winning clones exhibited shorter doubling times, greater maximum culture densities, and a growth advantages in pairwise competition relative to their precompetition ancestors, indicating the acquisition of adaptive phenotypes. To investigate the basis for mutator selection, we undertook a large series of pairwise competitions between mutator and wild-type strains under conditions where, in most cases, one strain completely overtook the culture within 18 days. Mutators were the most frequent winners but wild-type strains were also observed winning, suggesting that the competitive advantage of mutators is due to a greater probability of developing selectably advantageous mutations rather than from an initial growth advantage conferred by the polymerase variant itself. Our results indicate that under conditions where organism fitness is not yet maximized for a particular environment, competitive adaptation may be facilitated by enhanced mutagenesis.